Effectivity of 5% Temulawak Extract (Curcuma xanthorrhiza) on Post-Extraction Fibroblast Cells in Wistar Rats (Rattus norvegicus) - Anggayanti, Nyoman Ayu; Sudirman, Putu Lestari; Paramita, Made Indira (Padjadjaran Journal of Dentistry, 2023)
ABSTRACTIntroduction: Fibroblast is a key element in the wound healing process. During the proliferation phase, fibroblast cells are important for producing collagen and elastic cells. Curcuma xanthorriza is a medicinal herb that contains active compounds such as curcumin and flavonoid, both of which have the ability to increase fibroblast migration and accelerate wound healing. This study aims to observe the effectiveness of 5% temulawak extract (Curcuma xanthorrhiza) on post-extraction fibroblast cells in Wistar rats (Rattus norvegicus). Methods: The experimental study was conducted on 30 rats, divided into a control group and a treatment group. The subjects received intramuscular anesthesia prior to extraction of mandibular incisor. The treatment group was injected with 5% curcuma extract into their wound socket, while the control group was given placebo gel injection. The mandibular samples were obtained and analyzed on the 3rd, 5th, and 7th day. The number of fibroblast cells was observed using a light microscope with three different fields of view at 400x magnification. Results: The mean number of fibroblasts in the experiment group was higher than that in the control group. On the 7th day, the treatment group showed 342.50 fibroblast cells, while the control group only showed 298.25 cells. The number of fibroblast cells in the 3rd day treatment group was comparable to that in the 5th day of control group. Conclusion: It can be concluded that 5% temulawak extract (Curcuma xanthorrhiza) has a significant effect increasing post-extraction fibroblast cells in Wistar rats (Rattus norvegicus).